Agriculture and Culture Based Agrotourism: for the Development of Sibetan Village, Bali - sukanteri, ni putu; Tamba, I Made; Pratiwi, Ni Luh Putu Kirana (International Journal on Food, Agriculture and Natural Resources, 2024)
Global competition between tourism destinations is increasing, more and more countries are valuing tourism resources. The aim of the research is to analyze the prospects and challenges facing the development of natural resource-based agrotourism in tropical villages in Bali, analyze the physical assets owned by Sibetan village as an agrotourism destination (agrotourism in East Bali) Analyze agrotourism development strategies in Sibetan Village. This research was conducted in Sibetan Village, Banyakdem District, Karangasem Regency, Bali Province, Indonesia.  Research data was obtained from primary data regarding Sibetan village agrotourism, agrotourism activities, characteristics of agrotourism actors and agrotourism visitors at home and abroad. The research results show that the prospects and challenges for developing natural resource-based agrotourism in Bali are local culture that is open to general visitors and provides the experience of participating in cultural attractions in Sibetan Village. Challenges include weak promotion, the distance between agrotourism and the airport for national and foreign tourists and competition between agrotourism.  The physical assets owned by Sibetan Village are local culture which only exists in Sibetan Village, Sibetan Salak only found in Sibetan Village, and outhor recreation.  The strategy for developing agrotourism in Sibetan Village is to develop an aggressive strategy, so as to be able to create alternative agro-based tourism in Sibetan Village with superior Balinese salak products. The novelty of the research is agrotourism opportunities based on local cultural traditions, Sibetan snake fruit agricultural commodities, full participation from the community, government and management, collaborating with international tourism institutions and celebrity  for promotion